2020
DOI: 10.1111/are.14497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofAgave lechuguillaby‐product crude extract as a feed additive for juvenile shrimpLitopenaeus vannamei

Abstract: Agave lechuguilla is a succulent plant species, mainly distributed in the northeast of Mexico and south of the United States of America. The main use for this plant is the fibre´s extraction (known as Tampico fibres), resulting in 15% of fibres and 85% of a by‐product waste named guishe. The lechuguilla collectors, normally incinerate the guishe, thus causing environmental contamination. Interestingly, recent studies showed that guishe contains molecules with nutritional properties, such as saponins, flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We also assayed the nitric oxide values, obtained with the Griess reagent and nitrosylation profile by western blot (anti 3-nitrotyrosine), in isolated kidney mitochondria, and no significant differences were observed between the groups (data not shown). Crude extracts from lyophilized guishe were analyzed by Peña-Rodriguez et al, 2020 [11], identifying numerous bioactive phytochemicals, such as saponins and flavonoids. We suggest that they are responsible, alone or in combination, for various pharmacological activities, including antioxidant and hypolipidemic, because their chemical analysis revealed the presence of chlorogenin, diosgenin, diosgenin diglucoside, esmilagenin, hecogenin, manogenin, tigogenin hexose, yucagenin, and flavonols, such as quercetin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assayed the nitric oxide values, obtained with the Griess reagent and nitrosylation profile by western blot (anti 3-nitrotyrosine), in isolated kidney mitochondria, and no significant differences were observed between the groups (data not shown). Crude extracts from lyophilized guishe were analyzed by Peña-Rodriguez et al, 2020 [11], identifying numerous bioactive phytochemicals, such as saponins and flavonoids. We suggest that they are responsible, alone or in combination, for various pharmacological activities, including antioxidant and hypolipidemic, because their chemical analysis revealed the presence of chlorogenin, diosgenin, diosgenin diglucoside, esmilagenin, hecogenin, manogenin, tigogenin hexose, yucagenin, and flavonols, such as quercetin.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, their juice is used industrially for beverages and food additives [10]. Particularly, Agave lechuguilla is mainly distributed in the northeast of Mexico and is mainly used to extract fibers, resulting in 15% fibers and 85% of a byproduct waste named guishe [11]. Guishe is a bagasse left after fiber extraction; it is a vegetal pulp without any use.…”
Section: Introductionmentioning
confidence: 99%
“…The lechuguilla is also considered for uses in construction [ 18 , 19 ], soil and water decontamination [ 20 , 21 ], and bio-based polymers [ 22 ]. Likewise, other industrial fields, such as agricultural production [ 23 , 24 , 25 , 26 ], animal feed additives [ 27 ], agroindustry [ 28 , 29 ], nutraceuticals [ 30 ], and pharmacology [ 31 , 32 , 33 , 34 , 35 ] are interested in A. lechuguilla , especially for its active ingredients. Among the bioactive compounds of interest, Almaraz-Abarca et al [ 36 ] reported the presence of phenolic acid derivatives, flavonols, dihydroflavonoids, and glycoside flavonoids in the leaf extracts of A. lechuguilla .…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the characterization of phytochemicals in A. lechuguilla agro-residue, our research group identified 53 compounds among the flavonols, anthocyanidins, flavanones, and isoflavonoids, with a significant abundance of their glycoside derivatives [ 39 ]. Moreover, the crude extract of the lechuguilla residue, tested as a bioactive ingredient for farmed shrimps, showed health benefits that were attributed to its saponin and flavonol content [ 27 ]. These previous results support the valorization proposal of this constantly produced agro-residue.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of oral administration of enrofloxacin (ENR) and San‐Huang‐San (SHS), singly or in combination, on the survival performance, disease resistance and immunity of Litopenaeus vannamei were investigated (Zhai & Li, 2019). Pena‐Rodriguez et al (2020) evaluated the effect of Agave lechuguilla extract as a feed additive for L. vannamei . In the present study, complex Chinese herb medicine (the main ingredients were Codonopsis pilosula , Schisandra chinensis , Salvia miltiorrhiza , Eucommia ulmoides , Bupleurum chinense , Glycyrrhiza uralensis , Ligusticum chuanxiong and Lotus corniculatus ) was fed to shrimps to explore its effect on the growth performance, digestive enzyme activity, immunity and metabolism and Vibrio parahaemolyticus resistance of L. vannamei .…”
Section: Introductionmentioning
confidence: 99%